If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18b + -24b = -36 Combine like terms: 18b + -24b = -6b -6b = -36 Solving -6b = -36 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-6'. b = 6 Simplifying b = 6
| -39=q/9 | | 9-2j=8j-1 | | pi/2x=pi/220 | | 18g-12g=-30 | | 3x+38=13x-31 | | 5/4x+3/8x=48/12 | | C/4+1=x-4/6 | | 7h-3=4g+8 | | 15+7s=99 | | 4x+6=6x+8 | | 3/4y-30=-16.5 | | X/5+1=7/10 | | 4/3+2 | | -5+16x-5=22 | | X/4=5/10 | | 18=7+14b-25b | | 4-22x+10=4(5-6x) | | 3x-9-10x-2=4(x+7) | | (10/3)/2 | | r^3+r^2-r-1=0 | | 5y+2w= | | 9(5k-3)= | | -8u-6=-6u+6 | | 2l+4/3l | | 5+16n=5 | | 2x-6x-3=0 | | 6.2x+1=5.2x | | 2+3*16+1=85 | | 2.5=3.5x | | 64/(15-7)*2-9 | | -4-8(6z+4)=8(4z-7)-1 | | 7r=-1/2 |